A Pressure Sensing Device to Assist in Colonoscopic Procedures to Prevent Perforation—A Case Study - Kim, Se Eun; Kang, Young Jae; Jung, Chang Ho; Jeon, Yongho; Jung, Yunho; Lee, Moon Gu (Sensors, 2024)
Colonoscopy has a limited field of view because it relies solely on a small camera attached to the end of the scope and a screen displayed on a monitor. Consequently, the quality and safety of diagnosis and treatment depend on the experience and skills of the gastroenterologist. When a novice attempts to insert the colonoscope during the procedure, excessive pressure can sometimes be applied to the colon wall. This pressure can cause a medical accident known as colonic perforation, which the physician should prevent. We propose an assisting device that senses the pressure applied to the colon wall, analyzes the risk of perforation, and warns the physician in real time. Flexible pressure sensors are attached to the surface of the colonoscope shaft. These sensors measure pressure signals during a colonoscopy procedure. A simple signal processor is used to collect and process the pressure signals. In the experiment, a colonoscope equipped with the proposed device was inserted into a simulated colon made from a colon extracted from a pig. The processed data were visually communicated to the gastroenterologist via displays and light-emitting diodes (LEDs). The device helps the physician continuously monitor and prevent excessive pressure on the colon wall. In this experiment, the device appropriately generated and delivered warnings to help the physicians prevent colonic perforation. In the future, the device is to be improved, and more experiments will be performed in live swine models or humans to confirm its efficacy and safety.
Keywords: Case-studies; Colonic perforation; Colonoscope; Colonoscopy; Field of views; Medical Devices; Pressure sensing; Pressure signal; Quality and safeties; Sensing devices; Animals; Colon; Colonoscopes; Colonoscopy; Equipment Design; Humans; Intestinal Perforation; Pressure; Swine; colonic perforation; colonoscope; medical device; pressure sensor